(3feGPL hCeKdI ef GdRQGYI GdSYhOjIs - (3LdGd(B, (3GdedGMs ((3GdQjGV(B:s (3OGQ GdeQjN ddfTQ(B,s)
(3GdeTQhY GdRQGYj, OQGSI GdShb hGdJfHD HGdWdH, GdOQGSI GdafjI ddeTQhYGJ GdRQGYjI, GdOQGSI GdEbJUGOjI ddeTQhY, eaghe GdbjeI GdMGdjI ddfbhO, WQb heYGjjQ Jbjje GdeTQhYGJ, GdJbjje GdEbJUGOj ddeTQhYGJ, JNWjW heJGHYI GdeTQhYGJ GdRQGYjIs
(3HHdjhZQGajG(B: (3U(B.245s
Keywords: (3GdJNWjW GdRQGYjs; (3GdeTGQjYs; (3Jbjje GdCOGAs